Tensile behaviour of anti-symmetric CFRP composite - Wong, King Jye (2011)
This paper addresses the response of a 17-ply anti-symmetric carbon/epoxy composite subjected to uniaxial tensile loading. Hashin ply damage model is adopted to describe the damage behaviour of the plies, whereas damage initiation and progression of the interfaces are characterised by mixed-mode cohesive damage model. Force displacement curves obtained numerically and experimentally show good agreement. Results show that all laminae and interfaces experience the damage except laminae with 0 o fibre. In addition, damage is concentrated at the tab and central regions of the tensile specimen. Edge delamination is observed in all interfaces.